Renewable and Sustainable Energy: Current State and Prospects - Iglinski, Bartlomiej; Pietrzak, Michał Bernard (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The renewable energy sector is one of the fastest growing branches of the economy in the world, including in Poland. Extensive investigation in research centers results in the increased efficiency of obtaining energy from renewable sources, as well as a decrease in the prices of renewable energy installations. The development of renewable energy motivates further research and the development of new technologies. Investments in renewable energy may also benefit the local community by increasing the attractiveness of the region to tourists, creating opportunities for professional activation (especially in areas with high unemployment), increasing the competitiveness of the local economy and its energy efficiency and obtaining raw materials from local producers, mainly farmers, which are an additional source of income for them. Another possible economic advantage is charging lease fees, for instance, for land under wind turbines or fees for ground easement, in order to ensure access to the construction of power lines, e.g., connecting turbines to the grid; lowering heat prices for residents of a given town; building investment plots in or near heat plants and biogas plants, with the provision of heat and electricity at competitive prices directly from these plants; investors covering the costs of modernizing local roads; and creating new transmission, power lines and supply points.